A Large‐Scale Survey on Trauma, Burnout, and Posttraumatic Growth among Nurses during the COVID‐19 Pandemic. (27th October 2020) - Chen, Ruey; Sun, Chao; Chen, Jian‐Jun; Jen, Hsiu‐Ju; Kang, Xiao Linda; Kao, Ching‐Chiu; Chou, Kuei‐Ru
Abstract: A large‐scale survey study was conducted to assess trauma, burnout, posttraumatic growth, and associated factors for nurses in the COVID‐19 pandemic. The Trauma Screening Questionnaire, Maslach Burnout Inventory, and Posttraumatic Growth Inventory‐Short Form were utilized. Factors associated with trauma, burnout, and posttraumatic growth were analysed using logistic and multiple regressions. In total, 12 596 completed the survey, and 52.3% worked in COVID‐19 designated hospitals. At the survey's conclusion in April, 13.3% reported trauma (Trauma ≥ 6), there were moderate degrees of emotional exhaustion, and 4, 949 (39.3%) experienced posttraumatic growth. Traumatic response and emotional exhaustion were greater among (i) women (odds ratio [OR]: 1.48, 95% CI 1.12–1.97 P  = 0.006; emotional exhaustion OR: 1.30, 95% CI 1.09–1.54, P  = 0.003), (ii) critical care units (OR: 1.20, 95% CI 1.06–1.35, P  = 0.004; emotional exhaustion OR: 1.23, 95% CI 1.12–1.33, P  < 0.001) (iii) COVID‐19 designated hospital (OR: 1.24, 95% CI 1.11–1.38; P  < 0.001; emotional exhaustion OR: 1.26, 95% CI 1.17–1.36; P  < 0.001) and (iv) COVID‐19‐related departments (OR: 1.16, 95% CI 1.04–1.29, P  = 0.006, emotional exhaustion only). To date, this is the first large‐scale study to report the rates of trauma and burnout for nurses during the COVID‐19 pandemic. The study indicates that nurses who identified as women, working in ICUs, COVID‐19 designated hospitals, and departments involved with treating COVID‐19 patients had higher scores in mental health outcomes. Future research can focus on the factors the study has identified that could lead to more effective prevention and treatment strategies for adverse health outcomes and better use of resources to promote positive outcomes.